Anthropause Opportunities: Experimental Perturbation of Road Traffic and the Potential Effects on Wildlife - Perkins, Sarah E.; Shilling, Fraser; Collinson, Wendy (Frontiers in Ecology and Evolution, 2022)
The SARS-CoV-2 pandemic severely reduced many human activities. So pronounced was the change, it has given rise to the term ‘anthropause’: the considerable alteration of modern human activities. Among these was surface transportation, with prolonged traffic reductions, in excess, of 50% in many countries. Roads and traffic are responsible for functionally fragmenting ecosystems, wildlife populations, and species interactions. The unintentional “dialling-down” of traffic has given continuous monitoring systems of wildlife-vehicle conflict a unique opportunity to study the consequences of perturbing this source of wildlife disturbance and mortality. Experimental manipulation of traffic at the global scale would not have been possible without mitigation responses to SARS-CoV-2. Such a perturbation allows robust empirical investigation into wildlife responses to traffic, including changes in mortality, behaviour, genetic connectivity, and knock-on ecosystem effects, the responses to which can be replicated across a global network of wildlife-vehicle-conflict monitoring systems. We review the extent to which these extensive data-collection systems provide the primary source of data to study many of these responses, providing the raw material to understand some striking wildlife-consequences of the anthropause.